'You cannot talk about academic freedom in such an oppressive environment': perceptions of the We Will Not Be a Party to This Crime! petition signatories. (2nd October 2017) - Abbas, Tahir; Zalta, Anja
ABSTRACT: In January 2016, 1128 predominantly Turkish intellectuals signed an Academics for Peace petition to draw attention to the conflict in southeastern Turkey. Their actions were met with outcry from the government, accusing the signatories of disloyalty to the state, even treason. This paper is an analysis of the responses of 60 of these scholars to a questionnaire sent to the entire Academics for Peace email list. Respondents, including 58 signatories, provided various perspectives on academic freedom in Turkey, as well as their own experiences of signing the petition. We contend that the responses faced by these intellectuals illustrate the homogenizing effects of power to silence criticism and ensure loyalty to the government and its ideas of Turkishness. It reflects a continuation of the suppression of academic freedom in Turkey, an issue that sees little sign of abatement or reform in the light of present challenges.